2015
DOI: 10.1111/bjet.12264
|View full text |Cite
|
Sign up to set email alerts
|

Analysing content and patterns of interaction for improving the learning design of networked learning environments

Abstract: Learning Analytics constitutes a key tool for supporting Learning Design and teacherled inquiry into student learning. In this paper, we demonstrate how a Social Learning Analytics toolkit can combine social network analysis and content analysis for supporting a global and formal teacher inquiry. This toolkit not only supports teachers in improving the organisation of the learning process but also generates important input to improve the students' reflection on their own learning. Our examples show how combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 30 publications
(29 reference statements)
1
44
0
5
Order By: Relevance
“…Haya, Daems, Malzahn, Castellanos and Hoppe () consider the complex pedagogical framework of the JuxtaLearn project, which involves student production, team work and critical discussions between teams. Such situations, while very rich from a learning science perspective, are often hard to manage from a pragmatic point of view.…”
Section: The Papers In This Special Issuementioning
confidence: 99%
“…Haya, Daems, Malzahn, Castellanos and Hoppe () consider the complex pedagogical framework of the JuxtaLearn project, which involves student production, team work and critical discussions between teams. Such situations, while very rich from a learning science perspective, are often hard to manage from a pragmatic point of view.…”
Section: The Papers In This Special Issuementioning
confidence: 99%
“…A wide body of literature suggests that predictive learning analytics (PLA) can help teachers and institutions in general, to overcome such challenges, by identifying which groups of students might need extra support to reach desired learning outcomes (Conijn, Snijders, Kleingeld, & Matzat, ; Haya et al , ; Herodotou et al , ; Kovanović et al , ; Scheffel et al , ). For example, Scheffel et al () found that visualizing the relative performance of 172 students using the PLA supported the learning processes over time.…”
Section: Introductionmentioning
confidence: 99%
“…British Journal of Educational Technology Vol 50 No 6 2019& Matzat, 2017Haya et al, 2015;Herodotou et al, 2017;Kovanović et al, 2015;Scheffel et al, 2017). For example, Scheffel et al (2017) found that visualizing the relative performance of 172 students using the PLA supported the learning processes over time.…”
mentioning
confidence: 99%
“…Algunos estudios se han dirigido a analizar cómo una analítica del aprendizaje puede proporcionar a los profesores una visión profunda del proceso de aprendizaje (Fidalgo-Blanco et al, 2015;Haya et al, 2015;Rodríguez-Triana et al, 2015), mientras que otros han puesto el foco en el diseño de algoritmos que automatizan la minería de datos (Romero et al, 2007), o en la elaboración de propuestas visuales para presentar los resultados de los análisis (Mazza y Dimitrova, 2007;Valentín y Burgos, 2015).…”
Section: Discusión Y Conclusionesunclassified